Penanganan Pembiayaan Murabahah Bermasalah BMT Barokah Salaman - Aulya, Nur; Yeny Fitriyani; M. Pudail (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study reviews the causes and handling of problematic murabahah financing at BMT Barokah Salaman, including terminating financing as a last resort. The research method used is qualitative, with case studies through in-depth interviews, observation, and documentation. The research findings indicate that external factors, such as a decline in business income, and internal factors, such as weak feasibility analysis and inadequate financial education, are the causes of problematic financing. In terminating murabahah financing, this strategy is the last resort when members consistently fail to meet their obligations and peaceful approaches are no longer effective. The termination process includes evaluation, sending warning letters, final settlement meetings with members and their families, enforcing collateral, terminating financing relationships, recording them in an internal blocklist, and transparent documentation and reporting. This strategy is implemented by upholding the principles of fairness, careful consideration, and protecting all parties without causing injustice. This study emphasizes the importance of strong and humane risk management in maintaining the sustainability of Sharia microfinance institutions.